Energy frameworks and a topological analysis of the supramolecular features in in situ cryocrystallized liquids: tuning the weak interaction landscape via fluorination. Issue 46 (14th November 2016) - Dey, Dhananjay; Bhandary, Subhrajyoti; Thomas, Sajesh P.; Spackman, Mark A.; Chopra, Deepak
Abstract : The weak interactions assist in tuning the growth of π⋯π stacking with fluorine substitution in in situ cryocrystallized liquids. Abstract : Weak intermolecular interactions observed in crystalline materials are often influenced or forced by stronger interactions such as classical hydrogen bonds. Room temperature liquids offer a scenario where such strong interactions are absent so that the role and nature of the weak interactions can be studied more reliably. In this context, we have analyzed the common organic reagent benzoyl chloride (BC) and a series of its fluorinated derivatives using in situ cryocrystallography. The intermolecular interaction energies have been estimated and their topologies explored using energy framework analysis in a series of ten benzoyl chloride analogues, which reveal that the π⋯π stacking interactions serve as the primary building blocks in these crystal structures. The crystal packing is also stabilized by a variety of interaction motifs involving weak C–H⋯O/F/Cl hydrogen bonds and F⋯F, F⋯Cl, and Cl⋯Cl interactions. It is found that fluorination alters the electrostatic nature of the benzoyl chlorides, with subsequent changes in the formation of different weak interaction motifs. The effects of fluorination on these weak intermolecular interactions have been systematically analyzed further via detailed inputs from a topological analysis of the electron density and Hirshfeld surface analysis.